Water rights assessment for Beaver Creek National Wild River, Alaska - Van Haveren, Bruce P.; United States. Bureau of Land Management. Denver Service Center. Division of Resources. (Lakewood, Colo. : Bureau of Land Management, Service Center, Division of Resources, 1987)
"BLM/YA/PT-87/014+7200." "June 1987." Shipping list no.: 88-215-P. Bibliography: p. 107-113. U.S. Department of the Interior, BLM Alaska State Office. Mode of access: Internet.